Seasonal variation in productivity and nutritive value of Napier grass at Muguga, Kenya - Anindo, D.O.; Potter, H.L. (1994)
In a field study in Kenya, 55 plots in a Pennisetum purpureum sward were cut in rotation to give a 55-d regrowth cycle. After cutting, each plot was weeded and given 6.3 kg N + 4.5 kg P/ha. The daily DM production varied from 25 (dry season) to 178 kg DM/ha (rainy season). The mean DM yield after 55-d growth was 3.8 t/ha. In vivo (using Boran steers) DM digestibilities were 0.56 and 0.72 in the dry and rainy seasons, respectively, while the respective DM intakes were 2.5 and 2.7 kg/100 kg liveweight. CP content varied from 82 to 148 g/kg DM, lignin from 31 to 70 g/kg DM and NDF from 629 to 742 g/kg DM.